A review of the species of Oreichthys (Teleostei: Cyprinidae) in the Western Ghats, India - Knight, J. D. Marcus; Kumar, Rahul G. (Zootaxa, 2015)
Fishes currently assigned to Oreichthys cosuatis from the Western Ghats are shown to belong to a closely-related group of three valid species: Puntius coorgensis, which is raised from synonymy, and two new species, O. duospilus and O. incognito. Oreichthys coorgensis can be distinguished from its congeners by a combination of characters that include 22–23+1–2 scales in the longitudinal series with 5–8 pored scales; ½3/1/2½ scales in the transverse row; 6–7 predorsal scales and usually a faint blackish spot on the caudal-fin base. Oreichthys duospilus, sp. nov., can be distinguished by possessing an almost complete lateral line with 11–21 pored scales and two black spots: one on the dorsal fin and the other on the anal fin. Oreichthys incognito, sp. nov., can be distinguished by a lateral line with 5 pored scales; ½3/1/1½ scales in the transverse row; 8 predorsal scales and a vertical black bar on the dorsal fin.